Speechless complainer: a derridean reading of Titus Andronicus - Datlibeigi, Roohollah; Abbasi, Pyeaam (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The Roman tragedy of Titus Andronicus (1588-1593), the first and perhaps the least popular play of Shakespeare, depicts a non-Aristotelian tragic hero who is gradually decentred from his role and loses sympathy. Despite the fact that the play has been harshly criticised by many critics, Titus has regained its Elizabethan popularity in recent decades, and under the influence of postmodernist readings that focus on the play's fragmentary manner is well-matched with the fragmented contemporary time. This study is an attempt to present a detailed analysis of the language of Titus and the play in general. Using Derridean ideas, it will be argued that Shakespeare, through decentring the dualities of proper/improper language and speech/writing, decentres his protagonist and fills the play with chaos. It will be shown that the presence attributed to speech in Western thought is undermined by Shakespeare, for Titus’ ineffective speech makes him resort to writing which leads to even more chaos in the play. In other words, the Derridean logo centric presence is undermined both in Titus’ spoken and written languages and he can, either through neither speech nor writing, express his intentions. By and large, by decentring his protagonist, Shakespeare has endeavoured to distract the audience's attention from Titus and foreground Elizabeth's lack of a successor reflected in the play.